(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to analyze the implementation of the Tondano Watershed Management Policy in the province of North Sulawesi. This research uses the descriptive qualitative method. Research data are obtained from informants who are representatives of the society and government. The result of the study indicates that on the organizational aspect, Tondano watershed management institutions are very strongly supported by regulations under a strict legal umbrella for the management of the Tondano watershed, such as Law No. 41 1999 concerning Forestry, PP 37 2012 concerning watershed management, which is subsequently elaborated by North Sulawesi Provincial Regulation No. 1 2013 concerning the management of the Tondano watershed. In addition to that, Tondano watershed management involves many parties (multidisciplinary and multi-sector) in the Tondano watershed area. In the aspects of interpretation policy regarding the management of the Tondano watershed, it can be concluded that the implementor and stakeholders are able to master and know their duties and functions in the management of the Tondano watershed. In the aspect of application or implementation of Tondano watershed management policies based on existing regulations, however, a lot of plans in the form of programs and activities have been seen existing in every relevant agency, all of which are to make the Tondano watershed useful and sustainable. But in their implementation, these activities have not been carried out thoroughly by the regional government both in the province and district/city. The obstacle faced is the lack of commitment and presence of stakeholders in implementing watershed management based on existing regulations. Keywords: policy implementation, Tondano watershed management, organization, interpretation, application.